Diastolic function of right ventricular in patients with chagas disease who attend to the centro cardiovascular regional "Ascardio" Barquisimeto-estado Lara (Boletin Médico de Postgrado, 2017)
In the Undetermined Phase (IF) of Chagas Disease (ECh), alterations in diastolic function precede those of systolic function, with an early right ventricular (RV) condition. Doppler echocardiography has proven to be the non-invasive and innocuous method par excellence for evaluation. The RV diastolic function was determined by Doppler echocardiography in patients with ECh in IF who came to the C.C.R ASCARDIO echocardiography laboratory. The population consisted of 43 patients. Epidemiological, clinical and echocardiographic data were collected, namely: age, sex, time of diagnosis of ECh, maximum velocity (Vmax) of Wave E tricuspidea (Et) and A tricuspidea (At), relation E / At, deceleration time of E-tricuspide wave (TDEt), Vmax of Wave Et' and Relationship E / Et'. The data were processed with statistical package SPSS (Statisticial Pachkagefor Social Sciences) version 22, analyzed and expressed in frequency, percentage, mean and standard deviation. Results and conclusions: 74.4% of the patients were female and 25.6% were male, 30.2% of the population was between 61 and 70, 74.4% were between 6 and 10 years old Of the ECh, the mean and standard deviation of Vmax Et wave, Vmax wave At, E / A ratio, TDEt, Vmax wave Et'y and E / Et've ratio of 0.49 ± 0.09 m / S, 0.40 ± 0.09, 1.29 ± 0.31, 203 ± 57ms, 0.09 ± 0.02 m / s and 5.74 ± 1.85 respectively. The type of diastolic function that predominated was the normal one with 56%, being greater in the male sex with 81.8%.
Keywords: Doppler echocardiography; Chagas' disease; Diastolic function; Right ventricle; Indeterminate phase